The challenge of postmodernism to rationality in Practical Theology - Hugo, CJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
As with previous eras, the postmodern age presents great opportunity and grave peril for the church and to Practical Theology as an academic discipline. The article gives a meta-theoretical description and evaluation of the development of the theological rationality of Practical Theological paradigms. To enable the researcher to explore the challenge of postmodern paradigms, the article describes the rationality of the Newtonian epistemology, followed by a discussion of the ecosystemic and the communication actions approaches. Postmodernistic approaches are evaluated in view of the developments. The rationality of correlative approaches is described as a viable approach to the challenges of the postmodern culture. Two examples of South African researchers are discussed to illustrate the role of rationality in Practical Theology. It is proposed that a rationality of correlation poses a hermeneutical key to a practical theological paradigm.